Teknologi Penyiapan Pakan Protein Moderate dan Strategi Penyiapannya untuk Meningkatkan Produktivitas Maggot : Preparation Technology of Moderate Protein Feed and Its Strategy to Increase Maggot Productivity - Isnaini Dafri; Nahrowi; A Jayanegara (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
The aim of this research was to prepare moderate protein diet and evaluate its quality to increase maggot productivity. This research was conducted from the egg stage to the pre-pupae stage. One gram of larval eggs was used for each replication. The substrates used were fruit waste, household waste, and concentrate diet. This study used a completely randomized design with 2 treatments and 6 replications. Treatments were P0 (control feed of fruit waste and household waste) and P1 (moderate protein treatment feed). Control feed and moderate protein treatment were given as much as 13 kg during maintenance. The variables measured were dry matter consumption (grams), maggot weight (grams), pre-pupae percentage, substrate reduction (%), FCR, bioconversion (%), and WRI (Waste Reduction Index). Data were analyzed using paired sample T test. The results showed that BSF larvae receiving moderate protein treatment were significantly higher (p<0.05) compared to control feed for substrate consumption parameters, substrate reduction, and WRI. The conclusion from this research is the quality of feed with moderate protein content of 18,30 % which was prepared using a crude protein and energy balance approach was better than feed based on papaya fruit waste and household waste seen from the aspect of increasing substrat reduction, improving performance, prepupa metamorphosis, and increasing bioconversion of BSF larvae. Key words: bioconversion, larvae BSF, maggot, performance, waste